Development of Islamic Religious Education Teaching Materials Based on Work Ethic for Work Readliness og Vocational High School Students - Risna Astarina; Hendri Tanjung; Santi Lisnawati; Amir Tengku Ramly (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The work ethic material contained in the main Islamic Religious Education textbook is still general and does not adequately meet the needs of vocational high school students who will enter the workforce after graduation. A supplementary Islamic Religious Education teaching material addressing work ethic is needed for 12th-grade vocational high school students. The purpose of this study was to analyze the need for an Islamic Religious Education supplement on work ethic for 12th-grade vocational high school students, develop an Islamic Religious Education supplement on work ethic, and assess the feasibility of the Islamic Religious Education supplement on work ethic. This research is a Research and Development (R&D) study using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of the feasibility test for the Islamic Religious Education supplement on work ethic indicate that, in general, this supplement falls into the